THE EFFECT OF PROMOTIONS ON THE DECISION TO STAY AT BALCONE SUITES & RESORT IN BUKITTINGGI - Arija Bimbi Ramadhani; Kurnia Illahi Manvi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to determine how promotions influence the decision to stay at The Balcone Suites & Resort Bukittinggi. This study employs a quantitative descriptive research method with a causal-associative approach. A total of 98 respondents—guests who had previously stayed at The Balcone Suites & Resort Bukittinggi—constituted the study sample, selected using a non-probability sampling method. A Likert-scale questionnaire was distributed as part of the data collection process. IBM SPSS Statistics version 27 was used to analyze the data through descriptive analysis, testing of analytical assumptions, and simple linear regression analysis. Based on the research findings, the promotion variable, with an average score of 3.62, and the decision to stay, with an average score of 3.65, both fall into the “good” category. According to the results, guests’ decisions to stay at The Balcone Suites & Resort Bukittinggi are positively and significantly influenced by promotions, with a significance value of 0.039 (< 0.05). The regression coefficient of 0.219 indicates that a one-unit increase in promotion leads to a 0.219-unit increase in the decision to stay. Promotion accounts for 42.2% of the variation in guests’ decision to stay, while the remaining 57.8% is influenced by other factors not examined in this study.